Mendorong Optimalisasi Koperasi Desa dan BUMDes di Desa Cikurutug Sukabumi - Saleh, Munandi; Resian, Ragis Arginta; Destiana Safitri, Neng; Kurnia Gumulya, Nicholas; Waladiah, Siti Agnia (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
Cooperatives and Village-Owned Enterprises (BUMDes) play a strategic role in strengthening community-based economic development at the village level. Cikurutug Village, Cireunghas District, Sukabumi Regency, faces challenges in optimizing its cooperatives and BUMDes, particularly in governance, management, digital literacy, and limited business networking. This community service program aimed to strengthen institutional capacity, enhance managerial skills, and encourage the use of digital technology by cooperatives and BUMDes. The activity was carried out on August 26, 2025, involving 30 participants through a participatory method consisting of preparation, organization, training implementation, and evaluation stages. The results indicated an improvement in participants’ understanding from 45% before training to 82% after training. Moreover, 90% of participants considered the program beneficial, 80% were ready to apply the acquired knowledge, and 70% expected further assistance, especially in digital marketing. Therefore, this program successfully strengthened cooperatives and BUMDes in Cikurutug Village and opened opportunities to establish a more independent and sustainable village economic ecosystem.